Pencegahan karies gigi dengan pasta gigi herbal ekstrak metanol biji kakao pada murid SD Negeri 1 Pagar Air Aceh Besar - Mardiah, Ainun; Nuraskin, Cut Aja; Reca, Reca (Jurnal PADE: Pengabdian & Edukasi, 2024)
Dental caries is a disease caused by the interaction between bacteria debris and plaque, diet and teeth. Dental and oral diseases in Indonesia are 63%, Aceh province 47.0%, children 92.6%, and the elderly 96.2%. The Household Health Survey Report (SKRT) states that the prevalence of dental and oral diseases covers 60% of the population. Based on data obtained from SD Negeri Pagar Air, Ingin Jaya District, Aceh Besar Regency, 10 children, 70% have dental caries and 30% do not have caries. Cocoa bean methanol extract toothpaste contains secondary metabolic, alkaloids, flavonoids, saponins, and tannins with antibacterial properties, and is able to inhibit the growth of mutant streptococcus bacteria that cause dental caries. The purpose of community service is to increase the knowledge and awareness of students at SD Negeri 1 Pagar Air, Aceh Besar Regency, regarding the prevention of dental caries and the importance of maintaining dental health. The methodology used includes pretests and postes to measure students' knowledge before and after the intervention. The results of the pretest showed that the average knowledge score of students was 35 out of 100, while the results of the postes showed a significant improvement with an average score of 80 out of 100. This increase reflects that 80% of students now know how to brush their teeth correctly, 75% understand the causes of caries, and 85% realize the importance of using toothpaste. It is hoped that with the sustainability of this educational program, the level of dental and oral health among children can continue to increase.